Elasticity and flexibility of nucleic acid duplexes: A bio-physical perspective - Chhetri, Khadka B.; Lamichhane, Chitra P.; Subedi, Bhuban (Himalayan Physics, 2025)
The study of DNA, RNA, and PNA (peptide nucleic acid) molecules has various applications in fields such as drug design, nanotechnology, and electronics. Active biological processes like transcription, replication, recombination, protein synthesis, DNA repair, and DNA packaging require nucleic acids to undergo structural changes such as bending, stretching, and twisting under the influence of intercellular forces. To understand these processes, it is important to study their mechanical properties, such as Young's modulus, persistence length, and twisting rigidity. This work reviews the structural and mechanical properties of nucleic acid duplexes—RNA and DNA—including the PNA duplex. We found that the PNA duplex, which is capable of forming stable hybrids with DNA and RNA and has significant applicability in the field of drug design, is highly flexible in bending, stretching, and twisting compared to DNA and RNA duplexes. DNA exhibits greater bending flexibility but higher stretching rigidity than the RNA duplex.